Stablecoin-based digital trading and investment platforms and their potential in overcoming sanctions restrictions - Elena Vladimirovna Travkina; Alim Borisovich Fiapshev; Marianna Tolevna Belova (Economies, 2022)
The current article summarizes the main properties of stablecoins and explores their potential use in digital platforms to solve problems of supporting foreign trade and investment processes in countries subjected to restrictions on a wide range of its interactions with foreign countries, companies and international markets. Empirical results show that gold-backed stablecoins, being effective at hedging assets in certain situations, provide countries with the opportunity to distance themselves from traditional financial institutions and reserve currencies in the context of external operations. Digital trading and investment platforms created on its basis do not exclude the risks inherent to the instrument. Moreover, they are exacerbated by continuing and increasing sanctions pressure on the economy integrated with such platforms. However, at the same time, these assets remain one of the most effective ways to support foreign trade and investment processes in these countries. The thesis is proven using an informalized method based on expert evaluations regarding the possibility of digital platforms overcoming trade and investment sanctions, the effects of which on the Russian economy cannot yet be accurately predicted. The study proposes two scenarios for the development of these platforms, potentially expanding the boundaries of foreign trade and investment interaction of the country subjected to sanctions with international markets.
Keywords: 330; digital currencies; digital trading and investment platforms; economic sanctions; risks in business economics and finance; stablecoins